2013
DOI: 10.1038/nbt.2612
|View full text |Cite
|
Sign up to set email alerts
|

Image-based analysis of lipid nanoparticle–mediated siRNA delivery, intracellular trafficking and endosomal escape

Abstract: Delivery of short interfering RNAs (siRNAs) remains a key challenge in the development of RNA interference (RNAi) therapeutics. A better understanding of the mechanisms of siRNA cellular uptake, intracellular transport and endosomal release could critically contribute to the improvement of delivery methods. Here we monitored the uptake of lipid nanoparticles (LNPs) loaded with traceable siRNAs in different cell types in vitro and in mouse liver by quantitative fluorescence imaging and electron microscopy. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
1,134
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,185 publications
(1,191 citation statements)
references
References 46 publications
51
1,134
3
3
Order By: Relevance
“…Unlike other cationic vectors, these vectors induced little toxicity to cells, as well as normal organs (heart, live, kidney, lung, and spleen), thereby suggesting their better biocompatibility. Conventional vectors render gene escape from lysosomes to cytoplasm of target cells via a mechanism of “proton sponge effect,”26 yet this escape efficiency is extremely low at only 1–2% 12. Moreover, this process results in rupture of the lysosome membrane and, in turn, induces cytotoxicity 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other cationic vectors, these vectors induced little toxicity to cells, as well as normal organs (heart, live, kidney, lung, and spleen), thereby suggesting their better biocompatibility. Conventional vectors render gene escape from lysosomes to cytoplasm of target cells via a mechanism of “proton sponge effect,”26 yet this escape efficiency is extremely low at only 1–2% 12. Moreover, this process results in rupture of the lysosome membrane and, in turn, induces cytotoxicity 27.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these vector/gene complexes tend to accumulate in lysosomes followed by internalization, and subsequently the obtained gene escapes from lysosomes by taking advantage of the “proton sponge effect” into the cytosol of target cells, where they associate with the target gene to exert their silencing function 11. Unfortunately, the escape efficiency of genes from lysosomes into the cytosol is extremely low at only 1–2%, and it only occurs in a short limited time‐period when the vectors are located in a specific compartment that shares both early and late endosomal characteristics 12. Critically, during this trafficking process, significant lysosomal degradation of the gene by digestive enzymes and acidic conditions with a pH less than 4.5 occurs in lysosomes,13 thereby greatly diminishing the therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the siRNA protected by HGNs remain intact at neutral pH for at least a month, whereas overnight exposure to GSH at 0.01 × 10 −3 m releases half of the loading ( Figure S8, Supporting Information). However, the siRNA-HGN constructs accumulate in the endosome [38] and endosomal GSH levels are quite low. [39] Furthermore, release of siRNA from the endosome requires laser exposure, as shown by the unchanged GFP expression in both hESC and HeLa cells 6 d post siRNA coated HGN internalization ( Figure 4 and Figure S7 (Supporting Information)).…”
Section: Communicationmentioning
confidence: 99%
“…HCA was used to monitor lipid-based NPs loaded with traceable siRNAs in cell lines and in mouse liver cells i to quantify siRNA uptake and intracellular trafficking [81]. The lipid NPs comprised ionizable lipid/ distearoyl phosphatidyl choline/cholesterol/,PEG-DMG in ratios of 50:10:38.5:1.5 and entrapped antiGFP siRNA labeled with Alexa Fluor 647.…”
Section: Hca: Particulate Delivery To Access Intracellular Targetsmentioning
confidence: 99%
“…To date, no such genome-wide characterization of NP uptake has been reported, but small-scale studies are now adding further depth to the pharmacological studies. For example, in the HCA study of the uptake of lipid NPs outlined above [81], siRNAs were used to deplete cells of fundamental endocytic machinery, and showed that lipid NPs primarily endocytose by either clathrin-mediation or macropinocytosis. The parallel study using a limited number of siRNAs also found that macropinocytosis (as judged by depletion of Cdc42 and Rac1) was important for the internalization of this particle type [82].…”
mentioning
confidence: 99%